ANALISIS PENTINGNYA PENERAPAN SCHOLL WELL-BEING TERHADAP SOSIAL EMOSIONAL ANAK USIA DINI DI TK PUTRA MANDIRI 2 - Elisa Eka Putri; Eka Danik Prahastiwi (LPPM STAI La Tansa Mashiro, 2026)
Socio-emotional development is the main foundation of children's golden age, yet it is often overshadowed by educational focus on cognitive aspects. The concept of school well-being emerges as a holistic solution, emphasizing the importance of a safe, comfortable, and supportive school environment. This study aims to describe the implementation and its impact on the socio-emotional development at TK Putra Mandiri 2, including the ability to recognize emotions, show empathy, interact socially, and exercise self-control. Using a descriptive qualitative method through observation, interviews, and documentation, the findings reveal a strong and positive correlation. School well-being proves to be an inseparable determinant. When children's psychological needs are met, their potential develops optimally. Therefore, schools are advised to maintain a humane learning climate to foster a generation that is not only intelligent but also mentally healthy and socially mature.